Analisis Finansial Usaha Penangkaran Benih Padi Unggul di Desa Penggalaman Kecamatan Martapura Barat Kabupaten Banjar - Winda Sari Auliaturridha; Nina Budiwati; Luki Anjardiani (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The purposes of this study are to know the implementation of superior paddy seedling farming, and to analize the components of costs, revenues, income, profit and feasibility its farming. Technically, the farming technique of superior paddy between seedling and consumption purpose is almost similiar. The difference is only the seeds for superior paddy's seedling farming use the Stock Seeds (SS) class. The survey technique was used, and 43 farmers, who grew superior paddy for seedling purpose on Dry Season 2010, were selected purposively as respondents. The result revealed that he average total cost, production, revenue, income and profit per hectare was Rp 7,543,566; 2,324.37 kg; Rp 10,459,664; Rp 5,452,425; Rp 2,916,098, respectively. The average of RCR value was 1.37, which indicated that the superior paddy's seedling farming was financially feasible. Based on this study, government should determine the policy for certified-seed price certainty, in order to attract the farmers.